65 MRI-based predictive factors of axillary lymph node metastases in breast cancer. (18th September 2019) - Atallah, D; Moubarak, M; Arab, W; El Kassis, N; Chahine, G; Ghossain, M; Salem, C
Abstract : Objectives: To determine the accuracy of MRI in detecting axillary lymph nodes (ALNs) metastases preoperatively and to define predictive characteristics of ALN involvement in patients with invasive breast cancer. Methods: Breast MR (3 Tesla) examinations of 169 patients with invasive breast cancer were reviewed at Hôtel-Dieu de France Hospital. Morphological parameters in addition to apparent diffusion coefficient (ADC) value were compared with pathological nodal status. Results: The sensitivity and specificity of MRI in detecting ALN involvement were 87.5% and 55.6% respectively. The negative and positive predictive value of MRI was 81.64% and 66.34% respectively. The mean size of metastatic ALN was larger than that of negative ALN (13.9 mm vs. 10.9 mm, p = 0.000). ALNs larger than 12 mm were associated with higher risk of metastases (p = 0.000). The asymmetry of size between ipsilateral and contralateral ALNs was more significant in positive ALNs on pathology (p= 0.008 vs. 0.043). In a univariate analysis, the round shape of ALN, loss of fatty hilum, irregular contours and hypo-intensity/heterogeneous intensity on T2-weighted sequence were significantly predictive of lymph node metastasis (p = 0.000 for the four characteristics). In a multivariate analysis, only the round shape of lymph node and the hypo-intensity/heterogeneous intensity on T2-weighted sequence were significantly associated with lymph node metastasis (p=0.01 and p=0, 018 respectively). The ADC value of ALN did not aid the differentiation between benign and metastatic lymph nodes (p= 0.862). Conclusions: Conventional MRI using the ALN shape and the signal intensity in T2-weighted sequences can evaluate the axilla with high sensitivity.